The War Comes to Our Waiting Room - Matthew Anderson (Social Medicine Publication Group, 2006)
Nearly 10,000 kilometers separate Baghdad from our Community Health Center in the Bronx, the poorest of New York City's five boroughs. Officially, the United States of America is not at war with Iraq or Afghanistan; The United States Constitution designates the President as commander in chief of the armed forces, but reserves the power to declare war to Congress. Although Congress has not declared a war since December 8, 1941, we have fought major conflicts in Korea, Vietnam, and Iraq, as well as carried out countless "military actions" in all parts of the world. At the present time, our President says that we are involved in a "war against terrorism" and another "for the liberation of Iraq." Without a doubt, it has been primarily the Iraqi civilian population that has suffered devastating losses during this war, a fact that has been well documented in other parts of the world (see Medact's excellent reporting on the war in Iraq, available at: www. medact.org). However, war is also present in our community and in our medical practice. The fact that the weight of the war has primarily impacted our poor communities has tended to be invisible, so going forward we will try to make this impact evident.